Studi Pembuatan Briket Biomassa Berbahan Dasar Tempurung Kelapa dan Perekat Tapioka - Hadi Santoso (BEST, 2022)
One of the natural resources in Indonesia, especially Tarakan City, is the coconut plant. Coconut shells in Tarakan City are usually used for charcoal to be burned directly as an alternative fuel. This study aims to process charcoal from coconut shells into a more efficient fuel, that’s is biomass briquettes. Biomass briquettes from coconut shells are processed from charcoal making, milling, dough making, molding and drying. Coconut shell charcoal is mashed manually and combined with adhesive from tapioca flour with a ratio of coconut shell charcoal powder to tapioca flour powder is 5:1. Briquettes are printed in the form of tubes with a diameter of 4 cm and a length of 3 cm. The briquettes that have been molded are then dried in an oven at 110oC for 24 hours to remove the moisture content in the briquettes. In the study of application, it takes 10 minutes to cook 2 liters of water to a boil, which is equivalent to using a PGN gas stove with a medium flame setting, and in the process of cooking 2 liters of water it uses 602.8 grams of fuel with 390.2 grams of remaining fuel, and the efficiency is 37.14 %